Prototipe Penyiraman Otomatis Pada Tanaman Berbasis Internet Of Things Menggunakan Mikrokontroler Dan Sensor Kelembaban Tanah - Sri Damayanti; Yan Mitha Djaksana (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2022)
Ornamental plants are plants that are needed for beauty, in the care of ornamental plants they need water that must be met. If water needs are met then plant growth will be perfect. Therefore, this research makes it easier for farmers to work in terms of automatic watering, not only focusing on that, this research also designs how the tool works to detect the water content in the soil according to the needs of the soil or not. And the results of this study show that the prototype of automatic watering using a microcontroller based on the internet of things can simplify the way farmers work and save working time.